2017
DOI: 10.1016/j.jacc.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Mitral Valve Surgery Volume to Repair Rate, Durability, and Survival

Abstract: This study suggests that individual surgeon volume is a determinant of not only mitral repair rates, but also freedom from reoperation, and survival. The data from this study support the guideline's concept of reference referral to experienced mitral surgeons to improve outcomes in patients with degenerative mitral valve disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
171
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 209 publications
(185 citation statements)
references
References 18 publications
9
171
0
1
Order By: Relevance
“…52 A recent New York State-wide multicenter study has shown that individual surgeons' mitral valve case volume has a significant impact on early-and long-term patients' outcomes after mitral valve surgery. 53 Failure in mitral valve repair. Surgeons capable of successful and durable MV repair are not universally available.…”
Section: Watchful Waiting Strategy: Critical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…52 A recent New York State-wide multicenter study has shown that individual surgeons' mitral valve case volume has a significant impact on early-and long-term patients' outcomes after mitral valve surgery. 53 Failure in mitral valve repair. Surgeons capable of successful and durable MV repair are not universally available.…”
Section: Watchful Waiting Strategy: Critical Considerationsmentioning
confidence: 99%
“…Surgeons capable of successful and durable MV repair are not universally available. 53,54 On average, a surgeon needs to perform at least 100 isolated mitral cases per year in order to have a repair rate of 83%. A total annual surgeon volume of <25 operations has been reported to be associated not only with lower mitral valve repair rates, but also with increased 1-year mortality and mitral valve reoperation rates.…”
Section: Watchful Waiting Strategy: Critical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For most patients with severe primary MR, for example, it is well‐recognized that mitral valve repair is superior to mitral valve replacement . However, repair rates for primary MR vary significantly among individual surgeons and across institutions . Although repair rates for primary MR have increased, there remains concern that many patients with anatomy amenable to repair instead undergo valve replacement, with adverse downstream consequences related to LV dysfunction and the presence of valve prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with severe primary MR may have complex valve pathology that makes durable surgical repair technically challenging, such as anterior leaflet or bileaflet disease, Barlow's disease, or extensive annular or subvalvular calcification. The decision to operate on an asymptomatic patient with severe primary MR and preserved LV and systolic function is complex and hinges critically on the likelihood of a successful, durable repair in the hands of an experienced mitral surgeon working in collaboration with intraoperative echocardiographic imaging experts . In addition, the successful management of atrial fibrillation at the time of mitral valve surgery may require comprehensive approaches to ablation that are not widely practiced.…”
Section: Introductionmentioning
confidence: 99%